LAND SUITABILITY ASSESSMENT OF RICE CULTIVATION USING GIS IN VO NHAI, THAI NGUYEN, VIETNAM. - Nguyen Thi, Quynh; Pompe C. Sta Cruz , Pompe C. Sta Cruz; Tran Hai, Dang (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2022)
Vo Nhai is a moutainous district in Thai Nguyen, has complicated topography with population is almost of minority ethnics. The famers cultivate rice in the small plots, traditional practices and lack of consideration about the suitable factors leading to get low yield and rice quality. It is very important to choose suitable land for rice production in order to improve yield, quality and ensure food security. In this study, we used GIS associate with multi-criteria assessment to construct the suitable map for rice production for Vo Nhai District. Acording to FAO 1976 [4], we chosen 4 factors (temperature, rainfall, slope, soil type) that’s are deeply affected rice cultivation. The result of this study, there were 4,215 (ha) highly suitable area (S1) for rice production (5% total area Vo Nhai), 43,777(ha) moderately suitable area (S2) for rice production (52.1% total area Vo Nhai) and 36,068(ha) marginally suitable area (S3) for rice production (42.9 % total area Vo Nhai).